Studi Komparatif Rima dan Saja’ Dalam Stilistika - Mohamad Lahay; Rabiatul Adawiyah Ibrahim; M. Napis Djuaeni; Damhuri (Faculty of Education and Teacher Training, 2024)
Rhyme and saj' (rhymed prose) are forms of literary beauty in Indonesian and Arabic literature often used in poetry, pantun, and syair. Although there have been several studies on aspects of rhyme and saj', there is still a need for research exploring the correlation between these two literary styles. This study aims to analyze the differences and similarities between rhyme and saj' using literature study methods and comparative analysis. The results reveal eight components that were examined: rhyme placement at the beginning, middle, and end of lines; use of rhyme in multi-word phrases; phonetic similarity in letters; similarity of vowels (harakat) in phonetics; variations in rhyme patterns; and word balance harmony. Of these eight components, similarities between rhyme and saj' were found in four aspects: rhyme placement in the middle and end of lines, use of rhyme in multi-word phrases, and phonetic similarity in letters. Differences lie in the other four components: rhyme placement at the beginning of lines, vowel similarity in phonetics, variations in rhyme patterns, and word balance harmony. This research contributes significantly to the understanding of literary disciplines, particularly regarding rhyme and saj'. These findings are expected to enrich insights into the uniqueness and similarities between Indonesian and Arabic literary traditions, as well as open opportunities for further comparative studies in linguistics and literature.